Three decades of consumers’ environmentally friendly vehicles behavior: A comprehensive bibliometric network analysis and future research agenda - Ahmed M. Moustafa (Transportation Research Interdisciplinary Perspectives)
Environmentally friendly vehicles (EFVs) research has witnessed an exponential growth in recent years. In this article, we apply bibliometric network techniques to examine consumers’ EFVs behavior research based on 662 Web of Science (WoS) and Scopus documents written by 1590 authors representing 61 countries and spanning three decades (1993–2023). Results show that the most impactful journals publishing consumers’ EFVs behavior research are Energy Policy, Transportation Research Part A: Policy and Practice, Journal of Cleaner Production, Transport Policy, Technological Forecasting and Social Change, and Energy Economics. Furthermore, reference publication year spectroscopy (RPYS) was used to identify “citation classics” that lay the historical foundation for consumers’ EFVs behavior research. The thematic evolution analysis reveals that emerging trends in this domain are related to environmental concerns, total cost of ownership, and adoption intention. This study provides valuable insights for future researchers by mapping the evolution of EFVs research over the past three decades, revealing connections among influential authors, key nations, and leading institutions, and uncovering current trends within the broader field of consumers’ EFVs behavior.